Pendekatan Hubungan Internasional Terhadap Perlindungan Pengungsi : Menjelaskan Inisiatif Kebijakan Pemerintah Indonesia dan UNHCR - Cifebrima Suyastri (Frequency of International Relations (FETRIAN), 2020)
A major problem with this research is the arrival of refugee in Indonesia as a human security issue because this issue stems from the non-traditional concept of security that attracts international relations researchers, because of the presence of refugee from abroad without any regulation and explaining that refugees can threaten the stability of regional security. The arrival of refugees has implications on economic, social, environmental, and health problems for the host country. There was an immense amount of debate about the possibility of states adopting extraterritorial approaches to asylum processing and refugee protection, and about such policies’ compatibility with international refugee and human rights law. De-territorialize refugee protection and of UNHCR’s strategy in the evolving consultations. The issues of who, why, and how to protect refugees pose a series of normative challenges that can only be addressed by recognizing the dynamic nature of refugee protection today. Our answers have implications for institutional design. On one hand, this is a way of potentially making refugee protection sustainable in the long run. Some argue, however, that refugees acquire rights over time, which necessitates some kind of pathway to naturalization and ultimately citizenship. The most basic and significant norm of the international refugee regime emerges from the decision to allow states to take direct control of the process of refugee determination and to establish a legal framework permitting the screening of refugee applicants on a variety of national interest grounds. In this way, the refugee regime reproduces the state as the normal form of political organization, and the actor empowered to make life and death decisions over the human population. This research methodology is qualitative with literature study methods and case studies with a single instrument using participant observation techniques and in-depth interviews.